Development Strategy for Management Systems Strengthening Academic Accreditation Based on Strengthening Academic Accreditation at Islamic Religious Universities - Zainuddin Zainuddin; Yusuf Hadijaya; Muamar Al Qadri; Ismail Ismail; Ishak Ishak; Endah Retno Suci (Budapest International Research and Critics University, 2021)
The purpose of this study is to examine the strategy for developing a management system for strengthening the accreditation of study programs at Islamic religious universities through the use of literature study techniques such as observation, comparison of research journals, book collection, and other reading sources. Data analysis entails several steps, including data reduction, visualization, and conclusion drawing. According to the findings and analysis of the strategy for developing a management system for enhancing the accreditation of study programs for institutions, the strategy will focus on enhancing the accreditation of study programs at Islamic religious universities. According to his findings, the strategy for developing a management system for strengthening institutional study programs based on the strengthening of study programs at Islamic religious universities can have an effect on increasing the accreditation of service study programs, performance, governance, budgets, and the reputation of institutions and study programs. As demonstrated by the data in this study, implementing a management system development strategy centered on enhancing the accreditation of study programs at Islamic religious universities can result in a number of benefits, including the following: a) strengthening organizational governance; b) developing a strong knowledge base; c) cultivating a proactive culture of continuous improvement; d) adhering to applicable laws and regulations; and e) ensuring that, as a result, thinking centered on strengthening the accreditation of study programs has developed into a way of thinking that is embedded in stakeholders and decision makers throughout the organization.